Odpowiedzi

2009-10-17T19:52:12+02:00
A)-10/9+(-1/6)+9 3/4-(-6,25)= -10/9-1/6+9 3/4+6 1/4=-20/18-3/18+16=
-23/18+16=14 13/18
b)-5,8+2,7-2,2+0,3=-5,8-2,2+3=-8+3=-5
c)-0,2razy(-0,2)=0,04
d)-3 1/3razy(-3)=-10/3 razy -3 = 10
e) (-3)do potęgi drugiej razy 1/3=9 razy 1/3 =3
1 5 1
2009-10-17T19:54:27+02:00
A)-10/9+(-1/6)+9 3/4-(-6,25) = -10/9-1/6+39/4+25/4 = -20/18-3/18+64/4 = -23/18 +16 = 14 13/18
b)-5,8+2,7-2,2+0,3= -58/10+27/10-22/10+3/10= - 50/10 = -5
c)-0,2*(-0,2)= 0,04
d)-3 1/3*(-3)= 10/3*3 = 10
e) (-3)^2*1/3=9*1/3 = 3


1 5 1